Partisipasi Petani dalam Peningkatan Produksi Padi Sawah (Suatu Kasus pada Perkumpulan Petani Pemakai Air di Desa Lalousu Kecamatan Wonggeduku Kabupaten Konawe) - Jamrin, Jamrin; Tuwo, Muhammad Akib; Dirgantoro, Muhammad Arief (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to determine the participation of farmers in irrigation management and the level of farmer participation in increasing rice production. This type of research is a case study of predetermined subjects and objects. The method used in this study is a survey method, while the method for collecting data is a questionnaire. The population in this study were all farmers who were members of the P3A group. The sampling technique was carried out with Simple Random Sampling (simple random) with a sample of 46 farmers. Analysis of the data used to determine the relationship of participation of farmers using water in increasing rice production is the analysis of Chi-Square. The results of the study indicate that: 1) Participation of farmers in irrigation management activities is included in the high category or participating; and 2) there is a relationship between participation and production of paddy rice in Lalousu village, wonggeduku sub-district, konawe district.